2023
DOI: 10.1037/abn0000844
|View full text |Cite
|
Sign up to set email alerts
|

Delusion-like beliefs and data quality: Are classic cognitive biases artifacts of carelessness?

Abstract: There is widespread agreement that delusions in clinical populations and delusion-like beliefs in the general population are, in part, caused by cognitive biases. Much of the evidence comes from two influential tasks: the Beads Task and the Bias Against Disconfirmatory Evidence Task. However, research using these tasks has been hampered by conceptual and empirical inconsistencies. In an online study, we examined relationships between delusion-like beliefs in the general population and cognitive biases associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…We also attempted to replicate previous studies showing reduced sampling (e.g., fewer samples of evidence) in probabilistic reasoning, namely in the BT, associated with delusional ideation. After controlling for performance attentiveness, we reproduced Sulik et al’s (2023) 25 results in our subsample where we found no evidence of reduced sampling in probabilistic reasoning for participants higher in delusional ideation. This suggests that in subclinical psychosis, alterations in inferential processes attributable to sensory precision might be more prominent and detectable in the perceptual rather than in the cognitive domain.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We also attempted to replicate previous studies showing reduced sampling (e.g., fewer samples of evidence) in probabilistic reasoning, namely in the BT, associated with delusional ideation. After controlling for performance attentiveness, we reproduced Sulik et al’s (2023) 25 results in our subsample where we found no evidence of reduced sampling in probabilistic reasoning for participants higher in delusional ideation. This suggests that in subclinical psychosis, alterations in inferential processes attributable to sensory precision might be more prominent and detectable in the perceptual rather than in the cognitive domain.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find any significant relationship between psychotic-like experiences and ADJ. Although this BT behavioural pattern has been shown in schizophrenia patients with delusions 17,19,45 , it has repeatedly failed to be replicated in individuals from the general population with high scores for delusional ideation 25,40,46 .…”
Section: Psychotic-like Experiences and Cognitive Inferencementioning
confidence: 97%
See 3 more Smart Citations